1975
DOI: 10.1113/jphysiol.1975.sp010971
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of spinal motoneurones of normal and dystrophic mice.

Abstract: SUMMARY1. The properties of spinal motoneurones of normal and dystrophic mice (129/ReJ) were examined with intracellular electrodes.2. The following parameters of spinal motoneurones showed no significant differences between normal and dystrophic mice: resting and action potentials, the amplitude and duration of after-hyperpolarization, rheobasic current for excitation, threshold for excitation of the somadendritic membrane (IS-SD inflexion) and input resistance.3. The changes in motoneurone properties observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Conduction velocity of nerve impulses is reduced in these spinal root fibres (Huizar, Kuno & Miyata, 1975;Rasminsky, Kearney, Aguayo & Bray, 1978); the finding that the mode of conduction in some of these fibres is continuous implies that at least some of the bare axons are electrically excitable (Rasminsky et al 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conduction velocity of nerve impulses is reduced in these spinal root fibres (Huizar, Kuno & Miyata, 1975;Rasminsky, Kearney, Aguayo & Bray, 1978); the finding that the mode of conduction in some of these fibres is continuous implies that at least some of the bare axons are electrically excitable (Rasminsky et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Some of this ectopic activity is due to cross talk or ephaptic transmission between contiguous fibres within the spinal roots (Huizar et al 1975;Rasminsky, 1978a). Ephaptic transmission between mammalian axons also occurs as a transient phenomenon following acute injury of normal peripheral nerves (Granit, Leksell & Skoglund, 1944;Granit & Skoglund, 1945) and as a more stable phenomenon in experimental neuromas beginning about a month after nerve injury (Seltzer & Devor, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…A major difficulty for neurophysiological investigations has been to perform intracellular recordings from motoneurons in vivo in the adult mouse. Since the work by Kuno and colleagues (Huizar et al 1975;Kuno 1976) on the electrophysiological properties of spinal motoneurons in normal and dystrophic mice, no publications using intracellular recordings in vivo can be found in PubMed.…”
Section: Introductionmentioning
confidence: 99%
“…A major difficulty for neurophysiological investigations has been to perform intracellular recordings from motoneurons in vivo in the adult mouse. Since the work by Kuno and colleagues (Huizar et al 1975;Kuno 1976) on the electrophysiological properties of spinal motoneurons in normal and dystrophic mice, no publications using intracellular recordings in vivo can be found in PubMed.We have recently analyzed pyramidal excitation in the adult rat using intracellular recording from forelimb motoneurons (Alstermark et al 2004), and the work by Kuno and colleagues inspired us to attempt a similar analysis in the adult mouse. It will be shown that pyramidal stimulation evokes surprisingly weak excitation in forelimb motoneurons via the corticospinal pathway (different to rat) and that strong excitation is mediated via a fast reticulospinal pathway (similar to rat).…”
mentioning
confidence: 99%
“…Until recently, only a few groups had managed to perform intracellular recordings of motoneurons in vivo [2][3][4] , including our team who published a new preparation which allowed us to obtain very stable recordings of motoneurons in vivo in adult mice 5,6 . However, these recordings were obtained in paralyzed animals, i.e.…”
Section: Introductionmentioning
confidence: 99%